Translation Analysis of Simile and Metaphor Found in Olivia Rodrigo Album “Guts” - Ahzami Azka Musyafa (Universitas Sebelas Maret, 2026)
This research analyses simile and metaphor translation in six songs from Olivia Rodrigo’s “GUTS” album (All-American Bitch, Bad Idea Right?, Vampire, Lacy, Ballad of Homeschooled Girl, and Making the Bed). It identifies various types of simile and metaphor, analyses translation techniques used by translator, and assessed the translation quality focusing on accuracy and acceptability. Translating simile and metaphor is challenging because not all of them can be translated literally due to different cultures. There are found 109 data consisting of 23 similes and 86 metaphors. The researcher found three types of simile (animal, concrete-to-abstract, and synaesthetic) and four types of metaphor (anthropomorphic, animal, concrete-to-abstract, and synaesthetic). In The results reveal that there are three translation techniques proposed by Larson implemented by the translator. Besides, the translator also implemented his own technique. The analysis of accuracy shows that 8 similes and 24 metaphors are considered accurate, 9 similes and 48 metaphors are considered less accurate, and lastly 6 similes and 14 metaphors are considered inaccurate. The analysis of acceptability shows that 14 similes and 56 metaphors are considered acceptable, 7 similes and 30 metaphors are considered less acceptable, and 2 similes are considered unacceptable. The findings show that preserving the original imagery of similes and metaphors leads to the highest quality translations, supporting previous research.